INOVASI PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MAN 1 MOJOKERTO - Lailatul Ilmiyah; Anita Maghfiroh; Aufaa Dzakiy Ardinigrum; Nur Rachma Aryani; Husniyatus Salamah Zainiyati (UIN Antasari Banjarmasin, 2022)
Abstract. Curriculum development is very important to make it easier to achieve learning objectives. The PAI curriculum in madrasas (MI, MTs, MA) is currently still separate between each PAI subject (Qur'an Hadith, Fiqh, Aqidah, SKI) yet there is no complete integration into the main themes. Innovation in curriculum development really needs to be held, so that it doesn't just revolve around the same method, media but has its own value. This study aims to determine the innovation of Islamic religious education curriculum development at MAN 1 Mojokerto. This type of research is descriptive qualitative research. Data collection techniques in this study are observation and documentation. To innovate the PAI curriculum in madrasas, there are three perspectives that can be used as references, namely subject matter design, disciplines design, and broad filed design. One component of curriculum development is a strategy that includes methods. There are several learning methods, namely discussion methods, case studies, demonstrations and experiments, role playing, question and answer. We have encountered innovations in the development of Islamic education curriculum in Madrasahs using Subject Centered Design but have weaknesses that make the curriculum not getting better but more and more problems. One solution that can be used is the construction of the Madrasah's Collaborative Curriculum curriculum used at MAN 1 Mojokerto.Keywords: Innovation; Curriculum Developmen;, PAI; Madrasah.Abstrak. Inovasi pengembangan kurikulum sangat diperlukan untuk memudahkan mencapai tujuan pembelajaran. Kurikulum PAI di madrasah (MI, MTs, MA) saat ini masih terpisah diantara masing-masing mata pelajaran PAI (Qur’an Hadis, Fiqih, Aqidah, SKI) sehingga belum ada keterpaduan yang utuh dan terintegrasi ke dalam tema-tema pokok. Inovasi pengembangan kurikulum sangat perlu diadakan, supaya tidak hanya berputar pada metode, media namun memiliki nilai tersendiri. Penelitian ini bertujuan untuk mengetahui inovasi pengembangan kurikulum pendidikan agama Islam di MAN 1 Mojokerto. Jenis penelitian adalah penelitian deskriptif kualitatif. Teknik pengumpulan data yaitu observasi, wawancara dan dokumentasi. Untuk melakukan inovasi pada kurikulum PAI di madrasah, ada tiga perspektif yang bisa dijadikan acuan yaitu subject matter design, diciplines design, broad filed design. Salah satu komponen pengembangan kurikulum berupa pengembanga strategi meliputi metode pembelajaran yaitu metode diskusi, studi kasus, demonstrasi, eksperimen, bermain peran, dan tanya jawab. Inovasi pengembangan kurikulum PAI di Madrasah selama ini kita temui menggunakan Subject Centered Design tetapi mempunyai kelemahan yang membuat kurikulum tidak semakin baik melainkan semakin banyak masalah yang muncul. Salah satu solusi yang dapat digunakan ialah konstruksi kurikulum yaitu Madrasah’s Collaborative Curriculum yang digunakan di MAN 1 Mojokerto.Kata Kunci: Inovasi; Pengembangan Kurikulum; PAI; Madrasah.